Science Education in the Arab Gulf States: Visions, Sociocultural Contexts and Challenges - Mansour, Nasser (Springer, 2016)
The book introduces the development of science education in the Arab Gulf states and presents a critical analysis of current issues and concerns in educational research in science education. The key purpose is to provide some perspectives on the state of science education in Gulf and to share experiences with international scholars about the impact of the innovations and reforms implemented in science education in Arabian Gulf. But Science Education in the Arab Gulf States also intends to present new visions and to make suggestions and recommendations about the contribution of science education to prepare students in the knowledge age. The volume is organised into three main sections. The first section addresses the current practices and challenges in science education in some of the Arab Gulf states. This section sheds critically the light on the challenges and problems that hinder or constrain the implementation of innovations in science education. The second section analyses the science educational reforms and innovations that are being implemented in the Arabian Gulf. This section presents experiences and research with using new approaches to teaching and learning in science classrooms in some of the Arab Gulf states. The third section discusses the socio-cultural issues that have impacted on shaping and reshaping the science education in the Arabian Gulf. This section focuses on exploring the socio-cultural factors that influence engagement and non-engagement in science education. It also explores how socio-cultural issues and contexts guide the reform of science education in the Arabian Gulf and presents various examples of how we can respond to cultural issues.